Prokinetic effects of Citrus reticulata and Citrus aurantium extract with/without Bupleurum chinense using multistress-induced delayed gastric emptying models - Yanrong Gong; Xiaoxia Liang; Yanting Dai; Xiang Huang; Qiaozhen Su; Yan Ma; Fenglian Chen; Shuling Wang (Taylor & Francis Group, 2023)
AbstractContext Citrus aurantium L (Rutaceae) (Au) and Citrus reticulata Blanco (Rutaceae) (Ci) are commonly used as couplet prokinetics and Bupleurum chinense DC. (Umbelliferae) (Bup) is an herbal antidepressant in traditional Chinese medicine.Objective This study evaluates the synergistic prokinetic effects of Bup with Au and Ci in mice suffering from multistress-induced delayed gastric emptying (DGE).Materials and methods Kunming mice were divided into four groups: control, DGE, AuCi and AuCiBup. Mice were gavaged with AuCi (14.25 g/kg) or AuCiBup (22.13 g/kg) extract for 12 days. Gastric reminder rate, intestinal driving ratio, sucrose preference and open field test were examined, and serotonin (5-HT), motilin (MTL), substance P (SP), 5-HT4R and c-kit were assayed. Intracellular Ca2+ levels in primary cultured gastric smooth muscle cells (GSMCs) were determined.Results Both AuCi and AuCiBup treatment significantly reduced gastric residual rate (39.5% and 67.7%, p < 0.01). Higher serum levels of 5-HT, MTL and SP were observed in treatment groups (AuCi: 0.060 mg/L, AuCiBup: 0.089 mg/L, DGE: 0.025 mg/L, p < 0.01). The expression of 5-HT4R and c-kit in the antrum and duodenum was upregulated after treatment (AuCi and AuCiBup, 4.3-times, 2.8-times to DGE, p < 0.01). Medicated serums of AuCi and AuCiBup effectively increased the influx of Ca2+ into GSMCs in vitro (1.8-times, p < 0.01). In terms of 5-HT4R expression, circulatory contents of 5-HT and SP and Ca2+ influx, AuCiBup demonstrated better prokinetic effects than AuCi.Conclusions These findings indicate the potential for developing combination therapy with antidepressants and prokinetics in gastrointestinal dysmotility management.